Tractatus mythologicus Theorie und Methodik zur Erforschung von Mythen als Grundlegung einer allgemeinen, transmedialen und komparatistischen Stoffwissenschaft - Zgoll, Christian (Mythological Studies, 2019)
The volume is a programmatic manifesto for the new series MythoS. The author develops new methods - the hyleme analysis and the stratification analysis - and applies them on mythological materials, reconstructing myths as "Stoffe" and making them understandable in their polymorphic nature. In this groundbreaking work, the author sets the stage for a general theory of myth based on a new comprehensive, transmedial and comparative Stoff-research.